2001
DOI: 10.1149/1.1405998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Kinetics and Surface Emissivity on Chemical Vapor Deposition of Silicon in a Lamp-Heated Single-Wafer Reactor

Abstract: Chemical vapor deposition of Si in a lamp-heated single-wafer reactor is studied by monitoring the growth rate of films deposited on bare Si, silicon-on-insulator ͑SOI͒, and oxidized Si wafers. The growth rate is consistently higher for deposition of polycrystalline Si than for epitaxy of Si, due to different kinetics dictating the two depositions. Epitaxy of Si on SOI shows a higher overall growth rate than on bare Si. Likewise, deposition of polycrystalline Si on oxidized Si wafer with a 4000 Å thick oxide h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…6. As expected, the Si and SiGe growth rates are thermally activated [27], with an increase for Si (for SiGe) from 3 (4) up to 22 (18) nm min À1 as growth temperature increases from 615 1C up to 675 1C. The associated activation energies, E a (Si)=54.8 kcal mol À1 and E a (SiGe)=42.3 kcal mol À1 , are close to the Si-H bond strength (47 kcal mol À1 [28]) and in-between the Si-H bond strength and the Ge-H bond strength (37 kcal mol À1 [29,30]), respectively.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…6. As expected, the Si and SiGe growth rates are thermally activated [27], with an increase for Si (for SiGe) from 3 (4) up to 22 (18) nm min À1 as growth temperature increases from 615 1C up to 675 1C. The associated activation energies, E a (Si)=54.8 kcal mol À1 and E a (SiGe)=42.3 kcal mol À1 , are close to the Si-H bond strength (47 kcal mol À1 [28]) and in-between the Si-H bond strength and the Ge-H bond strength (37 kcal mol À1 [29,30]), respectively.…”
Section: Resultssupporting
confidence: 78%
“…We have thus investigated the specifics of the reduced pressure-chemical vapor deposition (RP-CVD) of Si and SiGe on both types of substrates. Some limited literature data have indeed shown that the Si growth rate can either increase [18] or decrease [19,20] when switching from bulk to SOI substrates. Both the buried oxide thickness and the overlayer thickness seem to have an impact on it [19,20], hinting at changes in surface temperature depending on the stack.…”
Section: Introductionmentioning
confidence: 99%
“…A significant Si growth rate reduction was also noted when switching from 1000 to 1500 ( A and finally 4000 ( A-thick BOX layers [16], in agreement with point (ii). As far as trend (iii) is concerned, it fits rather well with the data reported by Pejnefors et al [29] for large deposited Si thickness. They have indeed obtained Si growth rates that were slightly lower than on bulk for the first 150 nm deposited on top of the 50 nm thick Si over-layer of their SOI substrate, and then slightly higher.…”
Section: The Si Growth Kinetics On Patterned Soi Waferssupporting
confidence: 90%
“…2 is much lower on SOI substrates with 4000 ( Athick BOX layers than for other thickness. This is most probably due to changes in absorptivity and emissivity when the BOX thickness changes, which induce some surface temperature (and thus growth rates) variations for the same nominal growth temperature [29]; (iii) For longer deposition times, the Si growth rate converges towards the one on bulk, fullsheet wafers (7.6 nm min À1 ). The Si growth rate extracted from the next 30 min of growth (i.e.…”
Section: The Si Growth Kinetics On Patterned Soi Wafersmentioning
confidence: 99%
“…Some limited literature data have indeed shown that the Si growth rate can be vastly modified (usually reduced) when switching from bulk to SOI substrates [10][11][12]. Both the buried oxide thickness and the over-layer thickness seem to have an impact on it [11,12], hinting at changes in the surface temperature depending on the stack.…”
Section: Introductionmentioning
confidence: 99%